Clinical Characteristics and Short-Term Prognosis of Autoimmune Encephalitis: A Single-Center Cohort Study in Changsha, China - Deng, Shuwen; Qiu, Ke; Liu, Hui; Wu, Xiaomei; Lei, Qiang; Lu, Wei (Frontiers in Neurology, 2019)
Abstract Background and purpose: The incidence and prevalence of autoimmune encephalitis is gradually increasing. This retrospective observational study primarily aimed to analyze the clinical characteristics of autoimmune encephalitis patients in the Second Xiangya Hospital and report patient prognoses after immunotherapy. Methods: The clinical data of 86 patients who were diagnosed with autoimmune encephalitis from October 2014 to September 2018 were collected, and their corresponding clinical characteristics, laboratory examination, treatment, and outcome data analyzed. Results: In our study, 72 patients (83.7%) were positive for anti-NMDAR (N-methyl-D-aspartate receptor) antibody; 5 patients (6%) for anti-GABABR (γ-aminobutyric acid receptor-A) ; 4 patients (4.7%) for anti-LGI1 (leucine-rich, glioma inactivated 1); 3 patients (3.5%) for anti-Caspr2 (contactin-associated protein-like 2) (1 patient was positive for both anti-LGI1 and anti-Caspr2 antibodies); and 3 patients (3.5%) for onconeural antibodies. Among the 86 patients diagnosed as having autoimmune encephalitis, 50% showed acute disease onset (≤2 weeks). The most common inducing factor was fever or cold (17/86, 19.8%). The main clinical symptoms included, among others, psychiatric disturbances (82.5%), epilepsy (60.5%), autonomic dysfunction (58.1%), sleep disorders (45.3%), consciousness disorders (45.3%), and speech disorders (46.5%). No significant correlation between ICU admission rates and CSF or serum antibody scores was observed. However, CSF antibody scores of (+++) and (++) were associated with longer lengths of hospitalization (p < 0.05) and a higher CSF WBC count when compared with CSF antibody scores of (+) in patients with anti-NMDAR encephalitis (p < 0.05). Additionally, there was no significant correlation between mRS score difference on admission and discharge (after immunotherapy) and age, sex, and choice of immune treatment, while immune therapy taken within 15 days from onset was more inclined to be associated with an mRS score difference≥2 after immunotherapy in patients with anti-NMDAR encephalitis (p = 0.006). Conclusions: Autoimmune encephalitis has an acute or sub-acute onset and presents with psychotic symptoms, epilepsy, and autonomic dysfunction. The sex ratio in anti-NMDAR encephalitis was nearly balanced. Infection was a major factor inducing anti-NMDAR encephalitis, and the CSF antibody scores could be helpful in determining its prognosis since these scores showed associations with hospitalization duration and CSF WBC counts.